Chronic fatigue syndrome: An update - Shephard, R. J. (Sports Medicine, 2001)
The chronic fatigue syndrome is characterised by a fatigue that is disproportionate to the intensity of effort that is undertaken, has persisted for 6 months or longer, and has no obvious cause. Unless there has been a long period of patient- or physician-imposed inactivity, objective data may show little reduction in muscle strength or peak aerobic power, but the affected individual avoids heavy activity. The study of aetiology and treatment has been hampered by the low disease prevalence (probably <0.1% of the general population), and (until recently) by a lack of clear and standardised diagnostic criteria. It is unclear how far the aetiology is similar for athletes and nonathletes. It appears that in top competitors, overtraining and/or a negative energy balance can be precipitating factors. A wide variety of other possible causes and/or precipitating factors have been cited in the general population, including psychological stress, disorders of personality and affect, dysfunction of the hypothalamic-pituitary-adrenal axis, hormonal imbalance, nutritional deficits, immune suppression or activation and chronic infection. However, none of these factors have been observed consistently. The prognosis is poor; often disability and impairment of athletic performance are prolonged. Prevention of overtraining by careful monitoring seems the most effective approach in athletes. In those where the condition is established, treatment should aim at breaking the vicious cycle of effort avoidance, deterioration in physical condition and an increase in fatigue through a combination of encouragement and a progressive exercise programme.